Integrative Comparative Assessment of Cold Acclimation in Evergreen and Deciduous Iris Species - Lingmei Shao; Tong Xu; Xiaobin Wang; Runlong Zhang; Xiuyun Wang; Ziming Ren; Jiaping Zhang; Yiping Xia; Danqing Li (MDPI AG, 2022)
Cold acclimation (CA) is a strategy which plants have evolved to increase freezing tolerance. Global climate change could obstruct CA and raise the probability of winter injury, especially for evergreens. Hence, understanding the regulatory mechanism of CA is crucial to improve freezing tolerance in evergreen plants. A comparative study on a pair of closely related evergreen and deciduous iris species in response to cold through CA was conducive to uncovering and complementing the knowledge of CA. We investigated morphological, physiological and biochemical changes, as well as the expression of associated genes in the functional leaves of both iris species from natural CA to deacclimation. Briefly, fast and strong CA in the evergreen iris might cause early expressions of BAM1, NCED3, GPX6, etc., which leads to strong enzyme activity of starch degradation, abscisic acid biosynthesis and reactive oxygen species scavenging. Additionally, genes belonging to the antioxidant system were mainly induced during deacclimation. These results suggest that interspecies differences in the leaf freezing tolerance of irises are associated with the rate and degree of CA, which activates multiple signaling networks with complex interactions and induces the transcription of cold-responsive genes. Moreover, the ICE-CBF-COR signaling cascade may integrate and initiate diverse cold-responsive pathways during CA of the evergreen iris. The findings of this study provide valuable insight to further research on CA mechanisms and implicate genes which could support breeding strategies in herbaceous perennials under climate changes.